2021
DOI: 10.1002/ldr.3911
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term assessment of remediation treatments applied to an area affected by a mining spill in Spain

Abstract: This study evaluated the effectiveness of remediation treatments in the long-term (20 years) for one of the largest mine spills in the world, the Aznalcóllar accident. Soil recovery was carried out through the application of various rates of organic (compost and manure) and inorganic amendments (materials rich in iron oxides and calcium carbonate). Different amendment combinations were grouped in four treatments (T1 to T4) and applied in different sectors depending on the soil properties and the degree of init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The germination rate calculated for RA was very low (17.83 ± 3.54) respect to NC, suggesting the existence of phytotoxic concentrations of the metals in the soil that prevent plant emergence. In previous studies conducted in contaminated soils in the area, it was observed that the acidic pH value and the high concentration of metals resulted in a lack of available essential nutrients, a potential toxicity in soil solution, and an absence of vegetation [29,54]. Delgado-Caballero et al [67] found that low pH together with high concentrations of Cd, Pb and Zn could have increased the solubility and toxicity of these elements, inhibiting seed germination in Bouteloua dactyloides and Cynodon dactylon.…”
Section: Germinationmentioning
confidence: 98%
See 2 more Smart Citations
“…The germination rate calculated for RA was very low (17.83 ± 3.54) respect to NC, suggesting the existence of phytotoxic concentrations of the metals in the soil that prevent plant emergence. In previous studies conducted in contaminated soils in the area, it was observed that the acidic pH value and the high concentration of metals resulted in a lack of available essential nutrients, a potential toxicity in soil solution, and an absence of vegetation [29,54]. Delgado-Caballero et al [67] found that low pH together with high concentrations of Cd, Pb and Zn could have increased the solubility and toxicity of these elements, inhibiting seed germination in Bouteloua dactyloides and Cynodon dactylon.…”
Section: Germinationmentioning
confidence: 98%
“…Despite the efforts for restoring the area, metal(loid)s contamination persists more than 20 years after the accident. This soil is classified as eutric Regosol [31] and characterized by the absence of vegetation (Figure 1C) due to the presence of residual pollution [29,32]. Soil samples were collected from the surface layer (0-10 cm) using the methodology described in Aguilar et al [33].…”
Section: Soils and Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of these wastes is based on the needs of Technosols to cope with pollution; carbonated wastes (CW and MS) provide pH buffering capacity, organic wastes (WS, VC, and OL) support the recovery of biological activity, and iron-rich wastes (IO) promote the retention capacity of anionic metal(loid)s (e.g., As and Sb). The proportions of wastes in the different Technosols are based on the real doses applied in the field during the remediation actions [29]. The components of the Technosols were dried, sieved to <4 mm, and mixed manually in plastic trays.…”
Section: Production Of Technosolsmentioning
confidence: 99%